2020
DOI: 10.1038/s41598-020-64852-1
|View full text |Cite
|
Sign up to set email alerts
|

A Panoply of Rheumatological Manifestations in Patients with GATA2 Deficiency

Abstract: Purpose: To characterize rheumatological manifestations of GATA2 deficiency. Methods: Single-center, retrospective review of 157 patients with GATA2 deficiency. Disease course, laboratory results, and imaging findings were extracted. In-person rheumatological assessments were performed on selected, available patients. A literature search of four databases was conducted to identify additional cases. Results: Rheumatological findings were identified in 28 patients, out of 157 cases reviewed (17.8%). Twenty-two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Recently, rheumatological manifestations were found in 17.8% of patients in a study ( 38 ), and a correlation with a lower CD4:CD8 T cells ratio was found. Surprisingly, other than panniculitis, erythema nodosum, psoriasis and arthritis, non-immunologically mediated disorders such as piezogenic pedal papules and joint hyperextensibility were found in a significant number of patients, suggesting a role of GATA2 in collagen architecture.…”
Section: Clinical Features: Immunodeficiency Bone Marrow Failure and ...mentioning
confidence: 89%
“…Recently, rheumatological manifestations were found in 17.8% of patients in a study ( 38 ), and a correlation with a lower CD4:CD8 T cells ratio was found. Surprisingly, other than panniculitis, erythema nodosum, psoriasis and arthritis, non-immunologically mediated disorders such as piezogenic pedal papules and joint hyperextensibility were found in a significant number of patients, suggesting a role of GATA2 in collagen architecture.…”
Section: Clinical Features: Immunodeficiency Bone Marrow Failure and ...mentioning
confidence: 89%
“…An existing study investigated the role of GATA2 in IBD and determined that the GATA2 deficiency might influence the development of IBD. 28 Additionally, previous research identified that the transcription factor GATA2 serve as an inducer for the inflammatory reaction in colitis. 13 Furthermore, the current study demonstrated that the inhibition of GATA2 could contribute to downregulated AQP4 and blockade of PPAR‐α, thereby reducing the LPS‐induced apoptosis of M064 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, our findings elicited the elevation of GATA2 in the colon tissues of IBD patients and mice, and its silencing could reduce the LPS‐induced apoptosis of M064 cells. An existing study investigated the role of GATA2 in IBD and determined that the GATA2 deficiency might influence the development of IBD 28 . Additionally, previous research identified that the transcription factor GATA2 serve as an inducer for the inflammatory reaction in colitis 13 .…”
Section: Discussionmentioning
confidence: 99%
“…NADPH oxidase has shown to play an important role in regulating in antigen processing and cross presentation by DCs to antigen specific CD8+ T cells. Amogerina group (151)(152)(153), in both in vivo and in vitro using gp91phox deficient mice, demonstrated that DCs from gp91phox-mice were impaired in antigen degradation and MHC class I presentation to CD8+ T cells and activation of CD8+ T cells (148)(149)(150)156).…”
Section: Chronic Granulomatous Diseasementioning
confidence: 99%
“…Clinical features include recurrent infection (especially atypical mycobacterial infections, EBV, Pneumocystis jirovecii and recurrent HPV-related warts) and hematological malignancies (MDS/AML), pulmonary alveolar proteinosis (PAP), lymphedema, and sensorineural deafness. Rheumatological manifestations have also been reported ( 150 ).…”
Section: Congenital Defects Of Phagocyte Number and Functionmentioning
confidence: 99%